THE INTERACTION BETWEEN AGRICULTURAL AND ENVIRONMENTAL SUSTAINABILITY IN LITHUANIA: A REVIEW - Bužinskienė, Rita; Miceikienė, Astrida (PROFESSIONAL STUDIES: Theory And Practice, 2022)
This paper discusses the interactions between agricultural activities and environmental sustainability in Lithuania. This study focuses on two research problems: what is the interaction of agricultural activities for environmental sustainability; and what are preference sets of measures for environmental protection in agriculture. Literature review regarding trends in agriculture to the environment shows the relationship with negative affects. The interactions between agricultural activities and the environment are expressed as a negative impact in the fact for the too-high use of fertilization of nitrogen and phosphorus causes eutrophication of groundwater and terrestrial ecosystems. Overuse of irrigation causes salinization of the soil and the destruction of freshwater ecosystems. Chemical inputs expressed by the use of pesticides cause the loss of biodiversity. Irresponsible use of mechanized machinery has an effect on climate air pollutants and greenhouse gas emissions. Therefore, it is very important to apply a set of measures for environmental protection to agricultural activities. The results of the paper are useful for further research for „European Green Deal“ energy development